2002
DOI: 10.1002/yea.956
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux analysis of RQ‐controlled microaerobic ethanol production by Saccharomyces cerevisiae

Abstract: Microaerobic ethanol production by Saccharomyces cerevisiae CBS 8066 was investigated at different growth rates in respiratory quotient (RQ)-controlled continuous culture. The RQ was controlled by changing the inlet gas composition by a feedback controller while keeping other parameters constant. The ethanol yield increased slightly from the anaerobic values with decreasing RQ, reaching a broad maximum at RQ 20 to 12. There was little or no glycerol production at RQ values below 17 over a wide range of dilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 67 publications
8
47
0
Order By: Relevance
“…The data here showed that reducing the glycerol yield by 50% by glucose feeding monitoring led to a 20% decrease in the ethanol yield to the benefit of biomass (30%), acetate, and succinate compared to the reference fermentation (Table 1). When the formation of glycerol was reduced in a microaerobic ethanolic fermentation in continuous culture by a carefully controlled oxygenation, a decrease in the ethanol yield was also observed (8). RQ-controlled fermentation led to a lower maximum specific ethanol production rate and average ethanol productivity; however, it was possible to reach high ethanol production (85 g · liter Ϫ1 in 30 h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data here showed that reducing the glycerol yield by 50% by glucose feeding monitoring led to a 20% decrease in the ethanol yield to the benefit of biomass (30%), acetate, and succinate compared to the reference fermentation (Table 1). When the formation of glycerol was reduced in a microaerobic ethanolic fermentation in continuous culture by a carefully controlled oxygenation, a decrease in the ethanol yield was also observed (8). RQ-controlled fermentation led to a lower maximum specific ethanol production rate and average ethanol productivity; however, it was possible to reach high ethanol production (85 g · liter Ϫ1 in 30 h).…”
Section: Discussionmentioning
confidence: 99%
“….]) (3,4,8,11,12,19,31,40,42); another is to use genetically modified strains. Engineered strains were constructed by overexpressing and repressing components of the glycerol synthesis pathway (14,18,19,21,25).…”
mentioning
confidence: 99%
“…The condition number of the stoichiometric matrix was 89, indicating a numerically well-conditioned system. The anaerobic model is presented and discussed in detail elsewhere (14). However, some important points are also mentioned here.…”
Section: Methodsmentioning
confidence: 99%
“…The cellular protein and RNA contents were measured as described above. The biomass was assumed to contain 5% lipids under aerobic conditions and 2% lipids under anaerobic conditions (average lipid compositions) (14,31). Under anaerobic conditions, unsaturated fatty acids, ergosterol, and inositol were assumed to be taken up from the medium, while under aerobic conditions only inositol was provided in the medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation